2010
DOI: 10.7150/ijms.7.260
|View full text |Cite
|
Sign up to set email alerts
|

Changes of uterine blood flow after vaginal radical trachelectomy (VRT) in patients with early-stage uterine invasive cervical cancer

Abstract: Background. Vaginal radical trachectomy (RT) ligates and cuts several arteries supplying the uterus. Changes of blood supply to the uterus in two patients who experienced pregnancy and delivery were studied by using 3-D CT scanning. Effects of changes of blood supply to the uterus on the pregnancy courses were also examined.Methods. Vascular distribution in the uterus was studied in two patients who received vaginal RT after delivery. Effects of changes of vascular distribution after vaginal RT were studied wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…There is no strong evidence in current literature that fetal growth and placental function is affected with respect to the neovasculization [18] and healing process after an RT. In general, in an RT, cervix and upper vagina with a surrounding tissue of 1 -2 cm cuff of paracervical tissues are removed.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There is no strong evidence in current literature that fetal growth and placental function is affected with respect to the neovasculization [18] and healing process after an RT. In general, in an RT, cervix and upper vagina with a surrounding tissue of 1 -2 cm cuff of paracervical tissues are removed.…”
Section: Discussionmentioning
confidence: 89%
“…PPROM is a recognized complication and should be treated with 10-day course of erythromycin alone as a prophylactic antibiotic [18]. This has shown a statistically significant reduction in chorioamnionitis as well as a decrease in the number of babies born within 48 h and 7 days of PPROM onset [19].…”
Section: Discussionmentioning
confidence: 99%
“…19,20 This section of the uterine arteries induces an inadequate vascularization of the uterus and, consequently, an increased risk of miscarriage. 27 Manipulation of the uterus is increased when performing ART in comparison with VRT. This manipulation may induce an increased risk of miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, after ART, uterine vascularization derives only from the ovarian vessels, whereas after VRT, the ascending branch of the uterine artery is also preserved. 8,27 During VRT, even if uterine manipulation is limited, strong tractions on the uterus are performed and may create uterine vascularization problems. These tractions can induce an arterial compression, an ischemic process, and then an alteration of the placenta-fetal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In RVT, approximately half of the paracervical tissue is resected, including lymphatic and blood vessels and autonomic nerves together with about two thirds of the cervix. Doppler sonographic analysis showed that uterine artery fl ow is not altered [22,42] . However, the biological impact of altered uterine blood fl ow and changes of the anatomy have not been evaluated.…”
Section: Introductionmentioning
confidence: 97%